The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1002/j.1460-2075.1987.tb04803.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the beta-subunit of human prolyl 4-hydroxylase. This subunit and protein disulphide isomerase are products of the same gene.

Abstract: Prolyl 4‐hydroxylase (EC 1.14.11.2), an alpha 2 beta 2 tetramer, catalyses the formation of 4‐hydroxyproline in collagens by the hydroxylation of proline residues in peptide linkages. We report here the isolation of cDNA clones coding for the beta‐subunit of prolyl 4‐hydroxylase from a human hepatoma lambda gt11 library and a corresponding human placenta library. Five overlapping clones covering all the coding sequences and almost all the non‐coding sequences were characterized. The size of the mRNA hybridizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
226
0
1

Year Published

1995
1995
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 398 publications
(230 citation statements)
references
References 34 publications
3
226
0
1
Order By: Relevance
“…PDI can complement DsbA-deficient Escherichia coli, and increases the yield of heterologously expressed disulphide-containing protein in E. coli [21] and cultured insect cells [22] (DsbA is the E. coli periplasmic PDI homologue). PDI is also an essential structural subunit of the enzyme prolyl 4-hydroxylase (P4H) [23] and the microsomal triacylglycerol transfer protein (MTP) [24] in mammalian cells. Several other ER luminal proteins with high sequence identity to PDI have been identified (see below), and their putative functions have only recently started becoming apparent.…”
Section: Pdimentioning
confidence: 99%
See 1 more Smart Citation
“…PDI can complement DsbA-deficient Escherichia coli, and increases the yield of heterologously expressed disulphide-containing protein in E. coli [21] and cultured insect cells [22] (DsbA is the E. coli periplasmic PDI homologue). PDI is also an essential structural subunit of the enzyme prolyl 4-hydroxylase (P4H) [23] and the microsomal triacylglycerol transfer protein (MTP) [24] in mammalian cells. Several other ER luminal proteins with high sequence identity to PDI have been identified (see below), and their putative functions have only recently started becoming apparent.…”
Section: Pdimentioning
confidence: 99%
“…P4H, an ER luminal soluble enzyme that catalyses procollagen pro-α-chain prolyl hydroxylation, is a heterotetrameric (α # β # ) protein containing two PDI molecules as β-subunits [23]. Here, the function of PDI may be the retention or stabilization of the complex in the ER [109,110], although Wells et al [111] have shown that the β-subunit, as glutaredoxin, has dehydroascorbate reductase activity, and may therefore function in generating one of the cofactors of P4H, namely ascorbate.…”
Section: Subunit Associationmentioning
confidence: 99%
“…To identify new members of the PDI superfamily [6], we screened a human placental Agtl 1 cDNA library using human PDI cDNA [9,11] under conditions of low stringency. Through (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PDIR cDNA Human PDIR cDNA was cloned by screening a placental A, gtll cDNA library (Clontech) with a human PDI cDNA fragment [9,11], radiolabeled with [~-32p]dCTP (-220 TBq/mmol) (Amersham) using a random primer DNA labeling kit (Takara Shuzo). Hybridization proceeded at 37°C overnight in hybridization buffer [6 x SSC (1 x SSC: 0.15 M NaCI and 0,015 M sodium citrate, pH 7.0) containing 0.5% SDSa, 0.2% polyvinylpyrrolidone, 0.2% Ficoll 400, 0.2% BSA, and 20 #g/ml of sheared salmon sperm DNA], followed by a wash in 2 x SSC containing 0.1% SDSa at 37°C for 30 rain.…”
Section: Molecular Cloning and Dna Sequencing Analysis Of The Humanmentioning
confidence: 99%
See 1 more Smart Citation